Penggunaan Antibiotik yang Paling Hemat Biaya pada Pasien COVID-19: Studi Analisis Minimalisasi Biaya di Rumah Sakit - Yusransyah, Yusransyah; Udin, Baha (Universitas Islam Indonesia, 2023)
Background: Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) is the cause of COVID-19, a respiratory disease. One of the treatments administered to COVID-19 patients is antibiotics to prevent the occurrence of secondary infections. However, the budget allocation for antibiotic use issued by health facilities constitutes a considerable amount due to the significantly high demand, particularly among COVID-19 patients. This situation calls for pharmacoeconomic studies, such as cost-minimization analysis, for a better understanding and management of the financial implications.Objective: This study aimed to assess the economic value of antibiotics in a hospital within Tangerang District in 2021.Method: The method used in this study was non-experimental observation through the retrospective analysis of secondary data, consisting of patient costs and demographic information. The sample was selected based on inclusion and exclusion criteria. Furthermore, the collected data were analyzed using the Kruskal-Wallis test to determine a significant difference between the total cost in each therapy group.Results: In this study, 30 patients’ data met the inclusion and exclusion criteria consisting of 4 groups: ceftriaxone (n = 10), cefixime (n = 10), ceftazidime (n = 7), and cefadroxil (n = 3). Based on the calculation of cost-minimization analysis, the total average cost per patient for the ceftriaxone, cefixime, ceftazidime, and cefadroxil groups was 19,853,503 IDR, 13,330,545 IDR, 38,666,056 IDR, and 21,333,330 IDR, respectively.Conclusion: The results showed that the cefixime group has the most economical value.Keywords: Antibiotics, cost-minimization analysis, COVID-19, hospital